Phase 1, randomized, crossover study comparing intravenous GTX-104 to oral nimodipine in healthy human subjects - Amresh Kumar; Carrie D’Andrea; Prashant Kohli; S. George Kottayil; James Longstreth; R. Loch Macdonald (PLoS ONE, 2025)
Enterally-administered nimodipine is the only approved drug formulation available in the United States for treatment of patients with aneurysmal subarachnoid hemorrhage. Intravenous nimodipine is available in other countries but it contains a high concentration of ethanol that is irritating to the vasculature, can alter the effects of other medications, impair neurological assessments and is potentially harmful to the liver. We developed a sterile aqueous solution of nimodipine solubilized in polysorbate 80 micelles (GTX-104) that circumvents these problems. GTX-104 has been administered to 168 healthy human volunteers in 2 studies. We report the second study here, a phase 1, single center, randomized, 2-period cross over study that assessed the pharmacokinetics of GTX-104 and oral nimodipine capsules, which is the reference standard, in 58 healthy human volunteers. GTX-104 was administered for 72 hours as a continuous infusion of 0.15 mg/hour with a 30 minute bolus infusion of 4 mg every 4 hours. Nimodipine capsules were administered orally at a dose of 60 mg every 4 hours for 72 hours. The maximum plasma concentrations (geometric least square means) after the first dose of each formulation were similar (GTX-104: 63 ng/mL, n = 57 versus nimodipine capsules: 69 ng/mL, n = 56, ratio and 90% confidence interval [CI] of geometric LS means : 92% [90% CI: 82–104%]). The areas under the concentration-time curves on the 3rd day at steady state also were the same (GTX-104: 492 ng*h/mL, n = 56 versus nimodipine capsules: 462 ng*h/mL, n = 55, ratio and 90% CI of geometric LS means : 106% [90% CI: 99–114%]). The secondary pharmacokinetic parameters (daily maximum concentration at steady-state and time to maximum concentration) were also similar for the 2 formulations. The variability in PK parameters was less for GTX-104 compared to nimodipine capsules. The average oral bioavailability for nimodipine capsules was 7%. These results enabled a Phase 3 safety study of GTX-104 in humans with aneurysmal subarachnoid hemorrhage.